Chemical Composition of the Essential Oil of Cyperus Conglomeratus Rottb. from Iran - A. Feizbakhsh; A. Naeemy (E-Journal of Chemistry)
The compositions of the essential oil from cyperus conglomerates were obtained by hydrodistillation and analyzed by GC/MS (Gas chromatography/mass spectrometry). Twenty seven compounds were identified. Of which the cyperene (27.2%) was the major component. This is the first time that an oil of C. conglomerates has been found with cyperene as the major constituent. Also, the oil of C. conglomerates consisted mainly of sesquiterpene hydrocarbons, oxygenated sesquiterpenes and a small percentage of monoterpenes.